The research of influence of technological parameters SiC-C materials production process for fabrication face sealing collars of centrifugal pumps on their working behavior - Гнилиця, І.Д.; Криль, Я.А.; Цап, І.В. (Problems of Tribology, 2014)
The research of influence of inwardly pressed air on mechanical properties and working behavior of SiC-C materials was realized. Fixed fact that obtaining of continuous SiC-C materials without rifts is possible only if contents of small fraction 5-8 mkm less than 10-15% (the rest is fraction 50-100 mkm). After pressing and sintering under vacuum mechanical properties on 10-15% and wear resistance on 15-20% higher than in material pressed and sintered without vacuum.